Unraveling the Interconnection of Psychological Stability, Optimism, and Relational Competence among Adolescents - Rambar Lavanya,; Subramanian Kadhiravan, (The Bioscan, 2025)
Adolescents face numerous challenges along with the physical development tasks such as heightened academic pressure, social comparisons, identity formation struggles, and emotional instability. Psychological stability fosters coping with those issues and shapes their well-being. The objective of the study is to investigate the interconnection of psychological stability, optimism, and relational competence among adolescents. Psychological stability represents the overall function of an individual's feelings. Optimism reflects the ability of mental representation to look into the positive side of things, even in crucial situations. Relational Competence is the degree to which an individual engages in pro-social behavior and allows them to generate positive social adaptation with others across situations. The survey method was employed, targeting adolescents aged 13 to 19 years in and around Chennai city as the study population. An incidental sampling technique was used and data was collected from 346 adolescents with the help of the Perceived Social Competence Scale (II) by Anderson-Butcher, et al., (2014), Personal Optimism and Self-efficacy Optimism Scale (POSO) by Gavrilov-Jerkovic, et al., (2014), and World Health Organization's Well-Being Index (2004). SPSS version 25, was utilized to examine the relationships between variables, and, the results revealed that there is a significant positive correlation between selected variables. The mediating variable was found with the help of Amos Software version 23, the findings revealed that there is a full mediation of relational competence between optimism and psychological stability. The major findings and implications are presented in this article.